The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/1324065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Portland Cement with Gold Ore Tailings

Abstract: e disposal of gold ore tailings (GTs) has been a very difficult problem for a long time. us, this study explored a new approach to the management of GTs by preparing Portland cement. Physical properties, reaction mechanisms, and hydration product types of cement prepared with GTs (C-GTs) and ordinary Portland cement (C-SS) were compared. X-ray diffraction (XRD), thermogravimetric (TG), and scanning electron microscope energy-dispersive spectroscopy (SEM-EDS) analysis techniques were used to study the mineralog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…X-ray diffraction (XRD) analysis indicated that the hydration products of cement with GT were identical to those observed for cement without GT. The lack of detection of any diffraction peaks for C-S-H was attributed to the poor crystallization and amorphous properties of the C-S-H gels [97,114]. Based on Table 7, it was observed that the addition of 5% GT achieved the highest strength while further addition of GT caused a significant decrease in strength.…”
Section: Mine Tailingsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray diffraction (XRD) analysis indicated that the hydration products of cement with GT were identical to those observed for cement without GT. The lack of detection of any diffraction peaks for C-S-H was attributed to the poor crystallization and amorphous properties of the C-S-H gels [97,114]. Based on Table 7, it was observed that the addition of 5% GT achieved the highest strength while further addition of GT caused a significant decrease in strength.…”
Section: Mine Tailingsmentioning
confidence: 99%
“…Meanwhile, other researchers [113] suggested that the tailings should only pass through a 45 µm sieve. Wang et al [97] produced OPC clinker using gold mine tailings (GT) as a substitute for natural sandstone. The burnability analysis indicated that the GT had high reactivity.…”
Section: Mine Tailingsmentioning
confidence: 99%
“…It is interesting to visualize options of this type, given that tailings are mainly considered as waste, but have the potential to positively intervene in the circularity of the cement industry by promoting the reduction of virgin resource consumption such as limestone, bauxite, clay, sand, and gypsum (Wang, Yao, et al 2019). Cement production is an activity considered as one of the three industrial processes that have the highest environmental impact, together with the use of fossil fuels and the exploitation of land (Andrew 2018).…”
Section: Reuse (R2)mentioning
confidence: 99%
“…Earlier studies stated that GOTs can be utilized as partial replacement to the RS [13]. Wang et al [14] studied the physical properties, reaction mechanism, and hydration product types of cement prepared with GOTs.…”
Section: Introductionmentioning
confidence: 99%